STRATEGY IN TEACHING READING COMPREHENSION OF DESCRIPTIVE TEXTS: A LITERATURE REVIEW PERSPECTIVE - Mashur Mashur (Scientium Educational Review, 2022)
English is an international language that can be used to  support human needs in doing communication and interaction. In improving communication skills, students were required to have the ability in comprehension of a reading such as a descriptive text. Through reading activity, students got information, experiences and actions from the text. Moreover, the habit of reading would help students a lot in gaining new words and phrases to use in daily conversation. To have the ability, the student taught reading comprehension used KWL strategy. KWL strategy stands for Know-Want to Learn/Know-Learned. This strategy has three basic cognitive steps, namely accessing what the students Know, determining what the students Want to learn, and recalling what the students did Learn as a result of reading. In process of reading comprehension using KWL strategy involved prior knowledge, knowledge of text structure, and active search information. In this study, the researcher used a literature review in analyzing the applications of KWL strategy from various references and the study found that the KWL strategy was effective in teaching reading comprehension of English descriptive text. It also can improve the classroom atmosphere in teaching English for EFL learners.